Underlining Students’ Problems in Advanced Speaking Class at English Language Education Study Program - Yulieda Hermaniar; Alvina Rosyada Al Anis (UMBanjarmasin, 2022)
The shifting method from traditional face to face classroom to online classroom in an unavoidable phenomenon when the Covid-19 pandemic strikes Indonesia in early 2020.in university level, the speaking skill is an obligatory skill to be mastered by all students. Under normal condition, problems in speaking skill are commonly faced by students. Therefore, it becomes the researchers’ concern when the pandemic strikes as it will add students’ problem when the teaching and learning process are shifted to online class. In Advanced Speaking class, the researchers conduct study to carry out the problems in speaking class as result of the shifting method by distributing questionnaire. Using descriptive qualitative method, 19 students of English Language Education Study Program of STKIP PGRI Banjarmasin are taken as subject of the research. The result shows that the problems experienced by students are lack of vocabulary, pronunciation, grammatical error, lack of motivation, lack of confidence, anxiety, and shyness.